Generalized Robust Multichannel Frequency‐Domain LMS Algorithms for Blind Channel Identification - Chung, Ikjoo; Clements, Mark A. (ETRI journal, 2012)
Recently, several noise‐robust adaptive multichannel LMS algorithms have been proposed based on the spectral flatness of the estimated channel coefficients in the presence of additive noise. In this work, we propose a general form for the algorithms that integrates the existing algorithms into a common framework. Computer simulation results are presented and demonstrate that a new proposed algorithm gives better performance compared to existing algorithms in noisy environments.